Strategy for Revisit Intention Saba Baduy Culture - Didy Ika Supryadi; Taufan Handika; Daru Asih; Himawan Sutanto; Shine Pintor Siolemba Patiro; Dori Heza Morales (Universitas Mercu Buana, 2023)
Objective: The purpose of this study was to examine the effect of Service Quality, Destination Image, and Local Wisdom on Revisiting Saba Baduy Culture with Electronic Word of Mouth as an intervening variable.Methodology: This research was conducted using primary data, namely by distributing questionnaires online via Google form and disseminating through social media, namely Instagram, Line, and WhatsApp. The sampling technique used was purposive sampling. The population in this study was 115 respondents who were visitors to Saba Baduy spread across the Jakarta, Bogor, Bekasi, and Tangerang areas. The data was processed using Partial Least Square (Smart-PLS) version 3.2.9.Finding: The Baduy people are very careful with their customs and protect the natural surroundings. As they are aware that they live with nature and coexist with nature. The original Baduy tribe consists of the Inner Baduy and Outer Baduy. The Baduy tribe still maintains traditions, and customs and is anti-modern in terms of clothing, lifestyle, and others.Conclusion: An interesting conclusion found that when stakeholders build adequate infrastructure, this becomes something that does not reflect the authenticity of Baduy culture itself. On the other hand, tourists who want to return to the Baduy Traditional Villages since they want to experience nature which is still beautiful and serene, see the unique culture and local wisdom which is still very traditional, and experience the lifestyle of the Baduy people without modernization as it is seen as unique and interesting.